EFFECT OF FLY ASH AND GRANULATED BLAST FURNACE SLAG ON THE PHYSICAL PROPERTIES OF GEOPOLYMER CONCRETE USE CORAL SAND AND SEAWATER - Le, Hong Quan; Dong, Van Kien; Tran, Van Tuan; Nguyen, Van Chi (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
Geopolymer concrete is an eco-friendly material that possesses properties comparable to those of traditional Portland cement concrete. This study aimed to explore how the ratio of fly ash to blast furnace slag impacts the mechanical properties of geopolymer concrete using coral sand and seawater. Fly ash and blast furnace slag were used as binders alongside alkaline activators such as liquid glass and sodium hydroxide solution. The characteristics were assessed based on measurements of bulk density, water absorption, workability, compressive strength, and flexural strength. The compressive and flexural strengths of the samples increased gradually with the rising ratio of fly ash to blast furnace slag. Moreover, no significant differences were observed when comparing geopolymer concrete’s flexural and compressive strengths using coral sand and seawater with those using river sand and freshwater. On the other hand, the FTIR analysis results indicate that the characteristic Si-O-Si(Al) bond of the geopolymerization reaction in the wavenumber range 950 to 1005 cm-1 is present in both types of concrete, with no significant difference observed. These findings suggest that river sand and freshwater in geopolymer concrete production can replace coral sand and seawater for geopolymer concrete.